Biomonitoring trace metal contamination by seven sympatric alpine species in Eastern Tibetan Plateau. (December 2016) - Bing, Haijian; Wu, Yanhong; Zhou, Jun; Sun, Hongyang
Abstract: Biomonitoring permits determinations of trace metal contamination in remote areas like the high mountain ecosystems. In this study, six trace metals (Cd, Cr, Cu, Ni, Pb, and Zn) in seven sympatric alpine species (five tree species: Salix rehderiana, Populus purdomii, Betula albosinensis, Abies fabri, Picea brachytyla, and two dominant mosses: Pleurozium schreberi, Papillaria crocea ) at the Hailuogou Glacier foreland, Eastern Tibetan Plateau, were investigated to monitor their contamination. The concentrations of trace metals and Pb isotopic ratios ( 206 Pb/ 207 Pb and 208 Pb/ 206 Pb) in leaves/needles, twigs, bark, roots, and mosses were determined, and the biological factors and enrichment factors were calculated. The concentrations of Cd, Cr, Pb, and Zn in mosses were significantly higher than those in tree tissues and normal plants indicating the exogenous sources. The accumulation of trace metals (except Cd and Zn) was relatively higher in the tree roots, whereas their enrichments were significant in the leaves/needles and bark. According to biological factors, enrichment factors, and factor analysis, Cd, Pb, and Zn in trees and mosses were markedly impacted by anthropogenic emissions, whereas Cr, Cu, and Ni in trees were mainly from root adsorption from soils. The Pb isotopic compositions identified the anthropogenic Pb mainly from mining and smelting, coal combustion, and vehicle exhausts. The results indicated that mosses were still priority indicator of trace metal contamination from atmospheric deposition, and the leaves and bark of S. rehderiana, P. purdomii, and B. albosinensis were the better alternatives to monitor the atmospheric contamination of trace metals in the alpine ecosystem. Highlights: Trace metal contamination was monitored by seven sympatric alpine species in Eastern Tibetan Plateau. Cd, Pb and Zn were probably from mining and smelting, coal combustion and vehicle exhausts by atmospheric deposition. Cr, Cu and Ni in trees were influenced from root adsorption from soils. Moss is the best contamination indicator of atmospheric sourced metals. Leaves and bark of S. rehderiana, P. purdomii and B. albosinensis are better alternatives for trace metal contamination.